Localization of two cellular forms of the vesicular stomatitis viral glycoprotein. - Knipe, D M (1977)
Two cell-associated forms of the glycoprotein (G) of vesicular stomatitis virus, termed G1 and G2, have been resolved by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. G1 has the higher electrophoretic mobility, but both forms migrate more slowly than G protein synthesized in a wheat germ cell-free system (G0), which presumably is the unglycosylated form. G1 is a kinetic precursor of the G2 form, and the apparent cause of the electrophoretic difference between the two species is the presence of N-acetylneuraminic acid on the G2 form. Conversion of G1 to G2 occurs 10 to 20 min prior to the appearance of the G2 form of the protein on the cell surface. This suggests that the G protein may be completely glycosylated several minutes prior to its migration to the cell surface and that glycosylation is not the limiting step in its maturation. No glycoprotein comigrating with G0 can be detected in the infected cells, even after 5-min labeling periods; this suggests that partial clycosylation of G occurs concomitantly with or immediately after its synthesis.